The State of Sustainable Competitive Advantage Research and Future Directions - Toetik Wulyatiningsih; Deske W. Mandagi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
The growing importance of long-term competitiveness has intensified scholarly interest in sustainable competitive advantage (SCA). However, existing studies remain fragmented across strategic management, innovation, sustainability, and information systems research. This study conducts a systematic literature review supported by bibliometric and keyword co-occurrence analyses using the PRISMA framework to map the intellectual structure of SCA research. An initial search of the Scopus database identified 812 publications, which were screened and reduced to 136 articles for final analysis. The findings reveal six major thematic clusters: sustainability and stakeholder value, strategic management and organizational performance, innovation and technological capabilities, dynamic capabilities and organizational learning, industrial and manufacturing applications, and data driven and knowledge-based systems. The results indicate that sustainability strategies, managerial capabilities, innovation practices, operational systems, and digital technologies collectively shape the development of SCA. This study contributes by integrating fragmented insights and clarifying the main research streams in SCA literature. It also highlights emerging themes such as digital transformation and sustainability integration, offering directions for future interdisciplinary research on sustainable competitiveness.